On the formulation and application of design rules. (1st November 2017) - Szabó, Barna; Actis, Ricardo; Rusk, David
Abstract: Design rules are stated in the form of a predictor of failure initiation and its allowable value in the context of design of mechanical and structural components subjected to cyclic loading. Calibration and validation procedures are described and illustrated for the predictors with the aid of published experimental data. It is noted that mathematical models cannot be validated with respect to the allowable value of predictors.